2012
DOI: 10.1002/anie.201200101
|View full text |Cite
|
Sign up to set email alerts
|

Ionothermal Synthesis of Aluminophosphate Molecular Sieve Membranes through Substrate Surface Conversion

Abstract: Applications of zeolite membranes in separation, chemical sensors, and catalytic membrane reactors have led to extensive studies on their fabrication. [1,2] To date, mainly silicatebased zeolite membranes of the structure types MFI, [3] DDR, [4] LTA, [5] and FAU [6] have been synthesized on different substrates and evaluated for single-or multiple-gas permeation. Routes for the synthesis of zeolite membranes can be broadly classified into two categories: [7] in situ and secondary growth synthesis, both of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 39 publications
3
20
0
1
Order By: Relevance
“…These results indicated that the amount of Al dissolved by acid at ambient pressure was not sufficient to form ac ontinuous AlPO 4 -11 film without an additional Al source in the synthesis solution. In accordance with our observation, Tian and co-workers [21] also reported that aluminophosphate molecular-sieve membranes can only be ionothermally synthesized on d-Al 2 O 3 through substrate surface conversion in as ealed vessel. Electrochemical oxidation can effectively generate asuitable amount of Al ions precisely at the surface of the Al substrate without adding an Al source directly to the synthesis solution.…”
Section: Methylimidazolium Bromide ([Emim]supporting
confidence: 92%
“…These results indicated that the amount of Al dissolved by acid at ambient pressure was not sufficient to form ac ontinuous AlPO 4 -11 film without an additional Al source in the synthesis solution. In accordance with our observation, Tian and co-workers [21] also reported that aluminophosphate molecular-sieve membranes can only be ionothermally synthesized on d-Al 2 O 3 through substrate surface conversion in as ealed vessel. Electrochemical oxidation can effectively generate asuitable amount of Al ions precisely at the surface of the Al substrate without adding an Al source directly to the synthesis solution.…”
Section: Methylimidazolium Bromide ([Emim]supporting
confidence: 92%
“…The single gas permeation experiments were conducted at room temperature in an apparatus that was fabricated in-house [19]. The gas pressure p on the feed side of the membrane was maintained at 0.1 MPa, whereas the permeation side was at ambient pressure.…”
Section: Single Gas Permeation Measurementsmentioning
confidence: 99%
“…The CHA-type molecular sieve membranes were prepared according to the method reported elsewhere [19]. The typical synthesis procedure of the "substrate surface conversion" method can be described as follows: a d-aluminia disc was placed into a 1-ethyl-3-methyl imidazolium bromide ([EMIm]Br) solution containing reagent quantities of phosphoric acid (H 3 PO 4 , 85 wt% in water, AR), hydrofluoric acid (HF, 40 wt% in water, AR) and N-methylimidazole (N-MIm).…”
Section: Membrane Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…在之前的工作中, 我们探讨了离子热基底自转晶法 合成磷酸铝分子筛膜的机理 [14] : 离子热基底自转晶过 程中, 氧化铝基底表面与溶液中的磷酸和氢氟酸发生反 应, 可能在其表面形成前驱物, 前驱物进而成核、晶化 成分子筛膜.…”
unclassified